Digital Finance and Sustainable Development of Indonesian Banks - Variandy Tiaraputra; Fadhil Wicaksono; Susilo Toto Rahardjo (LifeSciFi, 2025)
This study aims to analyze the influence of the development of financial digital transformation on banking sustainable development, with a focus on banks listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. Using the Fixed Effect model, this study evaluates the relationship between the adoption of digital technology in the banking sector and banks' sustainable development in Environmental, Social, and Governance (ESG) aspects, as well as the influence of control variables such as bank liquidity and loan ratio. The results show that the digital transformation of finance has a significant effect on the sustainable development of banks, where more digitized banks tend to have better performance in sustainability aspects. In addition, bank liquidity and loan ratio are also proven to have a positive influence on bank sustainable development. However, bank size does not show a significant influence in this model. This study reinforces previous findings that digitalization in the financial sector can accelerate the achievement of sustainability goals, but also highlights the importance of other factors, such as managerial policies and sustainability-based strategies, in achieving these goals. This research contributes to policy makers in banking sector to formulate more effective sustainability strategies.